Perceptions of Bankers towards Issues of Islamic Banking in Pakistan - Rozeen Shaukat; Dr. Muhammad Asif Naveed (Journal of Islamic Thought and Civilization, 2020)
This study intended to investigate the current issues in the regulation of Islamic banking from the perspective of Islamic bankers in Pakistan. A cross-sectional survey of 165 bankers, recruited through stratified convenient sampling procedure, working at different Islamic banks in Lahore was conducted using a questionnaire. Descriptive statistics were applied using SPSS for data analysis. The results indicated that a large majority of the survey participants had postgraduate level of education, experience from 6-15 years, and belonged to either middle management or senior management. These participants perceived that limited role of policy institutions, gap in theory and practice, poor perception of people about Islamic banking, lack of short-term and long-term avenues, regulators’ preference of Shariah auditing rather than Shariah supervision, lack of financial services availability/branch networks, limited product offerings, non-availability of IB courts to resolve disputes, non-availability of research centres for Islamic banking, lack of trained staff, shortage of training opportunities and inadequacy of the curriculum for Islamic banking were the key issues faced by Islamic banking in Pakistan. However, the least issues that Islamic bankers faced were related to IB institutional and regulatory structures. The results generated evidence based pragmatic insights for policymakers and regulators in making strategic decisions for the development and growth of Islamic banking in Pakistan. This research makes a worthy contribution to the existing literature as no such study has addressed particularly the regulatory issues of Islamic banking in Pakistan.